MUÃ¡Â¸Â¤KAM-MUTASYÃ„â‚¬BIH Tafsir MuÃ¡Â¸Â¥ammad ÃŠÂ»Ã„â‚¬bid al-JÃ„ÂbirÃ„Â« atas Surah Ã„â‚¬li Ã¢â‚¬ËœImrÃ„Ân/3: 7 - Yahya, Mohamad (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
This article examines the interpretation of M. 'Ã„â‚¬bid al-JÃ„ÂbirÃ„Â« toward the concept of muÃ¡Â¸Â¥kam-mutasyÃ„Âbih in Surah Ã„â‚¬li'ImrÃ„Ân/3: 7. The topic is considered important because it has theoretical implications to various problems. The reason for the selection of al-JÃ„ÂbirÃ„Â« is due to its consistency in the use of a set of methodologies, namely historical criticism and structural analysis. Ã„â‚¬yat for al-JÃ„ÂbirÃ„Â« means sign. Ã„â‚¬yat muÃ¡Â¸Â¥kamah is a sign, an indicator, or reality of kauniyyah (universe reality) which shows that God is a God who is the Supreme One, while ayat mutasyÃ„Âbihah is a sign that God wants to set something out of the ordinary for His prophets and apostles as proof of their prophethood. Therefore, the term ar-rÃ„ÂsikhÃ…Â«n is a deep intellectual in science and knowledge, and they can know hermeneutical interpretation (at-taÃ¢â‚¬â„¢wÃ„Â«l wa at-tafsÃ„Â«r) of the mutasyÃ„Âbih verse (legally unclear verses) . Thus there is no verse of muÃ¡Â¸Â¥kam and verse mutasyÃ„Âbih in the sense that has been used, the verse which is legally clear and legally unclear. All verses of the Qur'an are very clear and can be understood by the community as the target of Islamic preaching at the time. Keywords Al-JÃ„ÂbirÃ„Â«, muÃ¡Â¸Â¥kam, mutasyÃ„Âbih.